Maximising nurses' and midwives' response rates to surveys - Cooper, A.; Brown, Janie (RCN Publishing Company, 2017)
Background: Low response rates to surveys have been a long-standing issue in research. This includes research involving nurses and midwives. To gain representative samples, appropriate measures to maximise response rates need to be used. Aim: To explore ways to maximise response rates from nurses and midwives, using a hospital-wide survey as an example. Discussion: All nurses and midwives at the study hospital were invited to participate in a survey. To encourage participation and elicit an adequate response rate, several strategies were used. A total of 1,000 surveys were distributed and 319 (32%) were returned. All the required age groups, levels of experience and types of nursing registration were represented in the responses and data saturation was achieved. Conclusion: It is important to pay attention to obtaining a representative sample. Further investigation of response rates to surveys by nurses and midwives is warranted. Implications for practice Strategies to maximise response rates from a target population should be used when conducting surveys.